Long Term Results of Primary Trabeculectomy at King Abdulaziz University Hospital - Osama M. Badeeb; Eman A. Al Hussain (Journal of King Abdulaziz University: Medical Sciences, 2023)
Long-term efficacy and safety of primary trabeculectomy +/- antimetabolite; assessed by a retrospective study of patients treated at King Abdulaziz University Hospital between, January 1988 and December 2007. Patients who had previous surgery, congenital glaucoma, or follow up in less than 3 years were excluded. Success defined as intraocular pressure ? 21 mmHg with and without medications. Fifty-nine eyes of 59 patients, 30 males and 29 females, with a mean age of 61.4 years were reviewed. Only patients who had primary open angle glaucoma met the inclusion criteria. Mean intraocular pressure was reduced from 25.1 to 16.3 mmHg, with and without anti glaucoma medications in 50 eyes (84.8%) at a mean follow up of 8.5 years. Success rate did not improve significantly (p < 0.7225) with antimetabolite. Life-table showed reduction of success rate over time; 96.6%, 81.2%, and 75.4% at 5, 10 and 15 years, respectively. There was a reciprocal significant association between success rate and the number of pre-operative topical medications (p < 0.0012), and argon laser trabeculoplasty of p < 0.0051). Trainees success rates were comparable to that of the principle author. No serious complication was seen. Nine eyes showed deterioration of vision, mainly due to cataract. Primary Trabeculectomy is safe, effective, and a suitable training procedure.